Analog Filters in Nanometer CMOS - Uhrmann, Heimo; Kolm, Robert; Zimmermann, Horst; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Starting from the basics of analog filters and the poor transistor characteristics in nanometer CMOS 10 high-performance analog filters developed by the authors in 120 nm and 65 nm CMOS are described extensively. Among them are gm-C filters, current-mode filters, and active filters for system-on-chip realization for Bluetooth, WCDMA, UWB, DVB-H, and LTE applications. For the active filters several operational amplifier designs are described. The book, furthermore, contains a review of the newest state of research on low-voltage low-power analog filters. To cover the topic of the book comprehensively, linearization issues and measurement methods for the characterization of advanced analog filters are introduced in addition. Numerous elaborate illustrations promote an easy comprehension. This book will be of value to engineers and researchers in industry as well as scientists and Ph.D students at universities. The book is also recommendable to graduate students specializing on nanoelectronics, microelectronics or circuit engineering.
Analog Filters -- CMOS Technology -- Operational Transconductance Amplifiers (OTAs) -- Gm-C Filters -- Current-Mode Filters -- Operational Amplifier RC Low-Pass Filter.
Keywords: Engineering; Electronics; Optical materials; Engineering; Electronics and Microelectronics, Instrumentation; Optical and Electronic Materials; Electronic Circuits and Devices